Surfactante com e sem lavado broncoalveolar em modelo experimental de síndrome de aspiração de mecônio - Henn, Roseli (2011)
BACKGROUND: Due to meconium's obstructive effect on the airways and its inhibitory action over the surfactant system, treatment with bronchoalveolar lavage and surfactant replacement are currently under evaluation. OBJECTIVE: To evaluate, in an experimental model, the effect on the arterial blood gases and pulmonary mechanics of the treatment of meconium aspiration syndrome with exogenous surfactant, preceded or not of bronchoalveolar lavage with diluted surfactant in low volumes. DESIGN/METHODS: 21 newborn piglets were mechanically ventilated with predetermined settings. Meconium aspiration syndrome was induced by instillation of 5 ml/kg of meconium 20% diluted in isotonic saline, and afterwards the piglets were randomly allocated to: group I (n=7) - control; group II (n=7) - surfactant (Curosurf®) 200mg/kg; group III (n=7) - bronchoalveolar lavage with diluted surfactant 5mg/ml (15 ml/kg in 2ml aliquots), followed by a supplementary dose of surfactant 125mg/kg. Arterial blood gases, compliance, resistance, and tidal volume were measured five times at specific intervals during the six hours of the study. RESULTS: After instillation of meconium, before treatment, the PaO2 fell to a mean of 50mmHg and the PaCO2 increased to 76mmHg (no statistically difference among groups). Mean PaO2 (mmHg) in groups I, II and III were 72, 106 and 172 (p=0,01); 70, 95 and 198 (p<0.01); 79, 110 and 217 (p=0.01) at 30 minutes, 3 and 6 hours after treatment, respectively. Mean PaCO2 (mmHg) in Groups I, II and III were 81, 65 and 35 (p=0.01); 82, 59 and 37 (p=0.01); 82, 75 and 32 (p<0.01) at 30', 3 and 6 hours after treatment, respectively. Mean Compliance (ml/cmH2O) in Groups I, II, III were 0.76, 1.01 and 1.57 (p<0.05); 1.02, 0.69, e 1.79(p<0.05) at 30 minutes and 6 hours after treatment, respectively. Mean resistance (cmH2O/L/S) in Groups I, II, III were 422.57, 385.29 and 268.86 (p<0.05); 408.83, 564.86 e 248.43(p<0.05) at 30 minutes and 6 hours after treatment, respectively. CONCLUSIONS: Bronchoalveolar lavage with diluted surfactant, with low volumes and small aliquots, followed by a supplementary dose of surfactant, significantly improved arterial blood gases and pulmonary function measurements when compared to the administration of a single dose of surfactant in an experimental model of meconium aspiration syndrome.